Recombinant human keratinocyte growth factor attenuates apoptosis in elastase induced emphysematous mice lungs. (2nd January 2017) - Kotnala, Sudhir; Baghel, Sumit; Verma, Deepali; Tyagi, Amit; Muyal, Jai Prakash
Abstract: Alveolar cell apoptosis is one of the potential factors involved in the pathogenesis of emphysema. Recently, exogenous recombinant human keratinocyte growth factor (rHuKGF) has been reported to induce the regeneration of gas exchange structures. Therefore, the rationale of the present study was to investigate the potential effect of rHuKGF in ameliorating tissue destruction in the emphysematous mice lungs. Four experimental groups (i.e. control-, emphysema-, therapy- and therapy control-group) were prepared. Subsequently, lungs from each mouse were collected for comet assay, elastase activity assay, antioxidant activity assay and real-time PCR based analyses. Comet assay analysis demonstrated the reduced tail DNA % and olive tail moment in therapy group. rHuKGF supplementation in emphysematous mice caused a significant reduction in the elastase activity levels along with reduction in activity of CAT, SOD and GPx. Furthermore, based on mRNA expression studies, the supplementation of rHuKGF ameliorated the induced apoptosis pathway in emphysematous mice lungs. Moreover, due to rHuKGF supplementation, TNF-α and p53 expression and production were markedly decreased in emphysematous mice lungs. Thus, therapeutic supplementation of rHuKGF might have reversed the alveolar cell loss in elastase induced emphysematous mice lungs by reducing DNA damage and maintaining antioxidant activities.